IPTEKS PENGOLAHAN IKAN SURIMI UNTUK USAHA KEMPLANG MIKRO - Dasir Dasir; Diah Isnaini; Erliza Yuniarti (Politeknik Negeri Sriwijaya, 2020)
River fish catches as the main raw material for making kemplang during the rainy season until the beginning of the dry season are very few, on the contrary the supply of river fish is abundant during the dry season to the rainy season. When there is an abundant supply of micro fish kemplang entrepreneurs stray the milled fish in a used refrigerator that is given ice cubes as a cooling with limited capacity, but the quality of the fish quickly drops. Surimi fish processing and storage training is given to overcome these problems. Fish processed with the surimi method can be stored for a long time and are not damaged, so that it can be used when the amount of river fish is limited and expensive. Besides discussing surimi method, this article also includes assistance in making kemplang and financial administration, with the hope that this community partnership program can improve the community's economy.